THE IMPACT OF DIGITAL TECHNOLOGIES ON INTERNATIONAL MARKETING AND TRADE MARKETING - Mamatkulova Shoira Jalolovna (Web of Journals Publishing, 2024)
The article examines the impact of digital technologies on international marketing and trade marketing. In the context of globalization and rapid development of information technologies, companies are faced with the need to adapt their strategies to effectively enter international markets. Digitalization of marketing improves communication with consumers, expands opportunities for data analysis and increases the accuracy of marketing campaigns. Also, digital tools can significantly improve interaction with partners in the field of trade marketing, optimize distribution processes and promote products taking into account the characteristics of each market. The article analyzes the main trends in digitalization in international marketing, as well as the impact of technology on trade marketing strategies and tools in different countries.
Keywords: digital technologies, international marketing, trade marketing, globalization, marketing strategies, digitalization, data analysis, distribution, marketing campaigns, innovative tools.